Das „Corpus der Urkunden der Römischen Herrschaft (CURH)“ Licht aus Scherben, Fetzen und Steinen - Haensch, Rudolf (e-Forschungsberichte des DAI, 2023)
The edicts and letters from Roman emperors, governors, and procurators preserved in inscriptions and on papyri form a important part of the documentary evidence used by classicists and jurists. The number of those documents is constantly increasing. Existing collections are outdated or only partial and unreliable. Given the diverse venues of publication and their distribution across the two disciplines of epigraphy and papyrology, it is extremely difficult for the individual scholar to get an overview. Therefore, under the direction of R. Haensch a comprehensive collection will be published over the next years, which will give access to those documents in their original form plus a translation and a detailed commentary. As first part a collection of edicts and letters from the praefecti Aegypti will be published.